History of medicine in Jagodina district - Jeremić Marko; Vuković Ana; Stanojlović Ninoslav; Vuković Rade; Marković Dejan (Serbian Medical Society - Dental Section, Belgrade, 2015)
The first record of scientific medicine in Serbia has been found in the early of 12th century. For centuries lifestyle, nutrition, natural environment, armies passing through, cultural heritage, and prejudice have affected healthcare in Serbia. Until 1820, Serbia has not had any educated doctor. Fourteen district physicians from 1839 and Dr. Karlo Beloni, to the last one, Dr. Selimir Đorđević - have spent part of their professional careers in Jagodina. All of them have had influence on raising health culture of Jagodina and its population and helped to overcome easily and quickly all existing diseases and epidemics. The Jagodina Hospital has been working without interruption for 147 years and represents one of the oldest healthcare institutions in Serbia.